2021
DOI: 10.5897/ajest2020.2916
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitude of Khat growing farmers on the safe use and handling of pesticides in Haromaya Wereda, Oromia Regional State, Eastern Ethiopia

Abstract: The awareness level of the farmers growing Khat regarding the safe use of pesticide was investigated in this study at Haromaya Wereda, Eastern Ethiopia. In order to achieve the proposed objectives, structured questionnaires, oral discussions, and field observations were organized with the farmers growing Khat on the safe use of pesticide. After the study sites were selected purposively, systematic random sampling of the target population was applied. The study result revealed that the farmers lack training on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
6
1
Order By: Relevance
“…Since children in this age range are unintentionally exposed to the poison, improper handling of the poison at home and elsewhere is evident. 19 The finding of this study is in contrary to the study conducted in Gondar, which found only one occurrence involving children under the age of 14 years. 15 Furthermore, 40% of this study participants were found in the age group of 11–20 years.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Since children in this age range are unintentionally exposed to the poison, improper handling of the poison at home and elsewhere is evident. 19 The finding of this study is in contrary to the study conducted in Gondar, which found only one occurrence involving children under the age of 14 years. 15 Furthermore, 40% of this study participants were found in the age group of 11–20 years.…”
Section: Discussioncontrasting
confidence: 99%
“… 8 A study conducted at Haramaya Woreda, which is one of the study areas of this study, reported poor knowledge and practice regarding the proper use, handling, and storage of pesticides among khat-growing farmers. 19 Similarly, another study conducted in Chiro, Eastern Ethiopia, identified low level of awareness regarding pesticide use in the community. 23…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Similarly, it has a low impact on neighboring/intercropped crops, stabilization of SWC structures, alternative on-farm activities for substantial returns, vulnerability to drought tolerance, and increasing national revenue generated from the crop, production rate and total population who depend on khat is skyrocketing in Ethiopia now [22].…”
Section: Khat Production Status In Ethiopiamentioning
confidence: 99%
“…16 Khat cultivators are increasingly employing pesticides to combat pests, insects, and diseases that have significant yield effects. 17 Some of the most common pesticides used by Khat growers include Malathion (diethyl(dimethoxy-thiophosphorylthio), Diatomaceous earth (silicon dioxide), Roundup (N(phosphonomethyl)glycine), DDT, Dacamine (2,4-Dichlorophenoxyacetic acid (2,4-D)), and Tricarnam (Carbaryl Propoxur). 6,16 Contact dermatitis, an irritating, inflammatory skin reaction to foreign materials, is one of the most prevalent occupational-related disorders among Khat farm workers, and because occupational dermatitis commonly affects the hands, low-wage employees may lose their ability to work and earn an income.…”
Section: Introductionmentioning
confidence: 99%